Characterization of a monoclonal antibody specific to California serogroup orthobunyaviruses and development as a chimeric immunoglobulin M-positive control in human diagnostics - Jordan A. Powers; Karen L. Boroughs; Sierra Mikula; Christin H. Goodman; Emily H. Davis; Elisa M. Thrasher; Holly R. Hughes; Brad J. Biggerstaff; Amanda E. Calvert (Microbiology Spectrum, 2023)
ABSTRACT California serogroup viruses (CSGVs) of medical importance in the United States include La Crosse virus, Jamestown Canyon virus (JCV), California encephalitis virus, and snowshoe hare virus. Current diagnosis of CSGVs relies heavily on serologic techniques for detecting immunoglobulin M (IgM), an indication of a recent CSGV infection. However, human-positive control sera reactive to viruses in the serogroup are scarce because detection of recent infections is rare. Here, we describe the development of new murine monoclonal antibodies (MAbs) reactive to CSGVs and the engineering of a human-murine chimeric antibody by combining the variable regions of the broadly CSGV cross-reactive murine MAb, 3-3B6/2-3B2 and the constant region of the human IgM. MAb 3-3B6/2-3B2 recognizes a tertiary epitope on the Gn/Gc heterodimer, and epitopes important in JCV neutralization were mapped to the Gc glycoprotein. This engineered human IgM constitutively expressed in a HEK-293 stable cell line can replace human-positive control sera in diagnostic serological techniques such as IgM antibody capture enzyme-linked immunosorbent assay (MAC-ELISA). Compared to the parent murine MAbs, the human-chimeric IgM antibody had identical serological activity to CSGVs in ELISA and demonstrated equivalent reactivity compared to human immune sera in the MAC-ELISA. Importance Orthobunyaviruses in the California serogroup cause severe neurological disease in children and adults. While these viruses are known to circulate widely in North America, their occurrence is rare. Serological testing for CSGVs is hindered by the limited availability and volumes of human-positive specimens needed as controls in serologic assays. Here, we described the development of a murine monoclonal antibody cross-reactive to CSGVs engineered to contain the variable regions of the murine antibody on the backbone of human IgM. The chimeric IgM produced from the stably expressing HEK293 cell line was evaluated for use as a surrogate human-positive control in a serologic diagnostic test.